From Crisis to Classroom: Preschool Teachers' Post-Earthquake Experiences - AYDOS, EMİNE HANDE; YAĞAN, SEVCAN; İPEK, ÖZTÜRK; Atabay, Yüksel Kantekin (Springer Nature, 2025)
Aim of the study is to explore the experiences of earthquake-affected preschool as they returned to their profession following the devastating February 6, 2023, earthquakes in Kahramanmara & scedil; in Turkey. These earthquakes, among the most destructive in the region's history, profoundly disrupted communities, including educators and children. The research addresses a critical gap by exploring how these natural disasters impact the teaching profession and educational practices. This phenomenological study with seven participants -six women and one man, aged 24-40- focuses on teachers from Hatay, Gaziantep, Kilis, and Malatya, collected via semi-structured interviews. Analysis followed a rigorous phenomenological approach to uncover the shared essence of their experiences. Findings reveal that teachers faced inadequate infrastructural preparations, including damaged schools and limited transportation. Psychologically, they felt unsupported, despite the limited training provided by the Ministry of Education. Housing and living conditions further compounded their struggles, with some teachers resorting to living in schools. For children, the study reports significant emotional, behavioral, and social changes. Earthquake-themed play and communication emerged as coping mechanisms, reflecting trauma, fear, and resilience. Teachers observed increased dependence, anxiety, and regressive behaviors such as thumb-sucking and bed-wetting among the children. Teachers assumed expanded roles as saviors, healers, and observers, focusing on creating safe environments, fostering resilience, and addressing both their own and the children's emotional needs. They adapted their classroom routines, shifting the emphasis from cognitive to social and emotional activities to aid recovery. Despite initial resistance, parents later recognized the value of resuming education in providing stability and healing for their children. The research underscores the critical role of teachers in disaster recovery, emphasizing their influence on children's emotional and psychological resilience. It calls for targeted disaster preparedness training for teachers, addressing their mental health needs, and prioritizing school infrastructure and resources. Collaborative efforts involving policymakers, educators, and mental health professionals are recommended to build a more robust educational response to natural disasters. This study highlights the transformative potential of education in emergencies, advocating for a proactive approach to equipping teachers and schools to navigate crises effectively while fostering long-term community resilience.
Keywords: Earthquake